Factors related to students' eating practices in three universities in Bogotá, Colombia (2015)
Objective To identify and describe eating habits of students from three universities in Bogota and factors influencing their adoption. Methods: Three focus groups were formed with an average attendance of 12 students from different undergraduate programs, between the ages of 18 and 25. The content of the accounts was analyzed and categorized according to the factors influencing the selection of food and eating habits. Results Students identified sensory and hygiene factors, the cost of food, the availability of food and available time to eat as the main factors influencing food selection. We also identified the influence of friends and family, among others, in their choices. Students who participated reported to prefer food from home, eating most of their meals at home and having eating schedules influenced by academic activities. Conclusion Although students have knowledge about what is good for them in terms of food, in university life, the organization of academic schedule, food availability and economic resources show significant influence on their habits and choices. Strategies to promote healthy habits in universities should then prioritize the control of such barriers. © 2015, Universidad Nacional de Colombia. All rights reserved.